A 27-Month-Old Boy with Polyuria and Polydipsia - Yvonne Lee; Erica Winnicki; Lavjay Butani; Stephanie Nguyen (Case Reports in Pediatrics)
Psychogenic polydipsia is a well-described phenomenon in those with a diagnosed psychiatric disorder such as schizophrenia and anxiety disorders. Primary polydipsia is differentiated from psychogenic polydipsia by the lack of a clear psychotic disturbance. We present a case of a 27-month-old boy who presented with polyuria and polydipsia. Laboratory studies, imaging, and an observed water deprivation test were consistent with primary polydipsia. Polydipsia resolved after family limited his fluid intake and began replacing water drinking with other transition objects and behaviors for self-soothing. This case highlights the importance of water deprivation testing to differentiate between causes of polyuria, thereby avoiding misdiagnosis and iatrogenic hyponatremia. Secondly, primary polydipsia can result during the normal stages of child development without overt psychiatric disturbances.